SECOND LANGUAGE IDENTITY AND STUDY ABROAD: BRAZILIAN EXPERIENCES IN THE SCIENCE WITHOUT BORDERS PROGRAM - Silva, Robson Ribeiro da (2017)
Higher education internationalization policies in Brazil have contributed significantly to boost international student mobility in the last decades. Aside from being considered a unique opportunity to acquire language proficiency, international mobility, along with its potential variables in L2 learning, has become the study focus of a new research field: Study Abroad (FREED, 1995; DUFOND, CHURCHILL, 2006). This area, which followed the trail cleared by SLA studies, started to catch the attention of applied linguists from the mid 1990s onwards. L2 identity, a key construct in this study, shows even more complex dimensions in intercultural contact in Study Abroad contexts. This study aimed to investigate how past participants of the Science Without Borders (SWB), the first Brazilian international mobility program launched by the Ministry of Education (MEC), refashioned their L2 identities. The impact of such experiences during the program in the deconstruction of language ideals held by the students was also studied, considering that linguistic exchanges took place between native and non-native speakers of English in a complex network of interactions. The research data were collected through a questionnaire and an interview, which were carried out with six past participants of the program and were eventually analyzed in the light of qualitative research. This study also approached the binarisms proposed by two SLA theoretical frameworks which have the native speaker as the only reference for the learner. The tenets of the CAT - Communication Accommodation Theory (GILES et al., 1987) and the AM - Acculturation Model (SCHUMANN, 1978), which suggest that L2 speaker linguistic competence is linked to how they adapt their way of speaking to that of the target language and culture, were approached and revisited. The results of this research indicated that, although the figure of the native speaker is still the main representation of English language and culture influencing Brazilians’ mentality, it was not the only one. Moreover, this study demonstrated that the SA experiences helped participants rethink their language learning beliefs and myths by relativizing English native speech patterns as absolute models. The interactions with speakers from different ethnolinguistic backgrounds afforded by the SWB were crucial to the reconstruction of their L2 identities through English.